2023
DOI: 10.3390/horticulturae9050580
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulants of Different Origins Increase Mineral Content and Yield of Wild Rocket While Reducing Nitrate Content through Successive Harvests

Abstract: Nowadays, biostimulant application is a sustainable practice with which to reduce inputs while maintaining crop yield and quality. Furthermore, the successive harvesting technique is also adopted to increase overall yield and reduce production costs in leafy vegetables. Therefore, a greenhouse experiment was performed to compare four different biostimulants, (i) two from enzymatic hydrolysate of Fabaceae species, (ii) one made from betaine, alginic acid and caidrin, (iii) and another one made from alfalfa extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Regardless of the application of biostimulants, the total yield (Figure 1) was lower compared to that of the recent findings reported by Caruso et al [32], being mainly attributed to our data originating from organic cultivation, which is inherently less productive than conventional methods. Furthermore, references to the literature indicate the potential for wild rocket to be harvested up to five times, especially during the winter-spring period, while our study reported total production for only three harvests [16,30]. As shown in Figure 1, the application of biostimulants, regardless of their origin, significantly increased total yield, corroborating the findings of Caruso et al [33] for rocket and Hassan et al [34], Mannino et al [35], Carillo et al [36], and Admane et al [37] for various crops such as tomato (Solanum lycopersicum L.), cucumber (Cucumis sativus L.), spinach (Spinacia oleracea L.), and lettuce (Lactuca sativa L.).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Regardless of the application of biostimulants, the total yield (Figure 1) was lower compared to that of the recent findings reported by Caruso et al [32], being mainly attributed to our data originating from organic cultivation, which is inherently less productive than conventional methods. Furthermore, references to the literature indicate the potential for wild rocket to be harvested up to five times, especially during the winter-spring period, while our study reported total production for only three harvests [16,30]. As shown in Figure 1, the application of biostimulants, regardless of their origin, significantly increased total yield, corroborating the findings of Caruso et al [33] for rocket and Hassan et al [34], Mannino et al [35], Carillo et al [36], and Admane et al [37] for various crops such as tomato (Solanum lycopersicum L.), cucumber (Cucumis sativus L.), spinach (Spinacia oleracea L.), and lettuce (Lactuca sativa L.).…”
Section: Discussionmentioning
confidence: 56%
“…However, the efficacy of biostimulants varies according to species and cultivar, environmental conditions, timing, and application methods, which makes standardizing their use challenging [29]. However, the strong interest of the scientific community and growers in the use of biostimulants, from both the perspective of a circular economy and in the context of sustainable agricultural practices that can be implemented in organic farming, has led to more and more studies setting themselves the goal of validating scientific protocols that clarify the mechanisms of action of the different biostimulants [30,31]. The different environmental conditions in the super-intensive production cycles typical of wild rocket cultivation, as well as the mechanical stress induced by cutting, can influence and vary the positive effects of biostimulants, making interpretations by farmers complex.…”
Section: Introductionmentioning
confidence: 99%